Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acsnano.2c06977
|View full text |Cite
|
Sign up to set email alerts
|

Core, Coating, or Corona? The Importance of Considering Protein Coronas in nano-QSPR Modeling of Zeta Potential

Abstract: To control stability in a biological medium, several factors affecting the zeta potential (ζ) of nanoparticles (NPs) must be considered, including complex interactions between the nanostructure and the composition of the protein corona (PC). Effective in silico methods (based on machine learning and quantitative structure–property relationship (QSPR) models) could help predict and characterize the relationship between the physicochemical properties of NP and the formation of PC and biological outcomes in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The dynamic light scattering (DLS) analysis revealed that the average hydration size of DAIEPMs (235.4 nm; Figure D) was slightly larger than that of AIEPMs (182 nm; Figure E) and increased with an increasing concentration of TCBPEME (Figure S2), which is probably caused by the loading of more AIEgens into the microspheres. The zeta potential analysis showed that the surface charges of DAIEPMs (−51 mV; Figure F) and BAPFPMs (−47.53 mV; Figure F) were negative, demonstrating their good dispersion stability in aqueous solutions . The absorption intensities of DAIEPMs ranged from 300 to 400 nm and were considerably higher than those of BAPFPMs; moreover, the characteristic absorption peak at 520 nm was retained, which may verify the simultaneous loading of the two AIEgens (Figure G).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The dynamic light scattering (DLS) analysis revealed that the average hydration size of DAIEPMs (235.4 nm; Figure D) was slightly larger than that of AIEPMs (182 nm; Figure E) and increased with an increasing concentration of TCBPEME (Figure S2), which is probably caused by the loading of more AIEgens into the microspheres. The zeta potential analysis showed that the surface charges of DAIEPMs (−51 mV; Figure F) and BAPFPMs (−47.53 mV; Figure F) were negative, demonstrating their good dispersion stability in aqueous solutions . The absorption intensities of DAIEPMs ranged from 300 to 400 nm and were considerably higher than those of BAPFPMs; moreover, the characteristic absorption peak at 520 nm was retained, which may verify the simultaneous loading of the two AIEgens (Figure G).…”
Section: Resultsmentioning
confidence: 85%
“…The zeta potential analysis showed that the surface charges of DAIEPMs (−51 mV; Figure 2F) and BAPFPMs (−47.53 mV; Figure 2F) were negative, demonstrating their good dispersion stability in aqueous solutions. 28 The absorption intensities of DAIEPMs ranged from 300 to 400 nm and were considerably higher than those of BAPFPMs; moreover, the characteristic absorption peak at 520 nm was retained, which may verify the simultaneous loading of the two AIEgens (Figure 2G).…”
Section: Assembly Of Lateral Flow Immunoassay Test Stripsmentioning
confidence: 84%
“…The average particle size distribution in this study was 47 nm, which is optimal for passing through biological cells. The zeta potential is an important parameter that reflects the physicochemical properties and biological stability of produced nanoparticles [93–95] . It is used to measure the surface charge and, consequently, the stability of nanoparticles [96] .…”
Section: Resultsmentioning
confidence: 99%
“…The zeta potential is an important parameter that reflects the physicochemical properties and biological stability of produced nanoparticles. [93][94][95] It is used to measure the surface charge and, consequently, the stability of nanoparticles. [96] The zeta potential of the encapsulated E. intermedia extract was found to be 33 mV, while the same parameter was reported to be 12 mV for the liposomal extract of green tea.…”
Section: Investigation Of Particle Size and Zeta Potential Of Synthet...mentioning
confidence: 99%
“…Although this approach is still in its infancy, a recently proposed model considers the protein corona assessment for the prediction of the zeta potential of ENMs. [40] Figure 3. The toxicity of NPs on the gastrointestinal tract.…”
Section: Ingestion Exposure Routementioning
confidence: 99%